2022
DOI: 10.1002/mc.23404
|View full text |Cite
|
Sign up to set email alerts
|

Role of hemoglobin alpha and hemoglobin beta in non‐small‐cell lung cancer based on bioinformatics analysis

Abstract: The differentially expressed genes (DEGs) were identified and screened differentially in non‐small‐cell lung cancer (NSCLC) using information from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus databases, and the correlation of DEGs in protein interaction, function, and pathway enrichment were analyzed to search for new biomarkers and potential therapeutic targets for NSCLC. Protein–protein interaction network (PPI) analysis showed that CDK1 and GNGT1 were the most significantly upregulated hub nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“… 23 These results indicated that HBB had an inhibitory effect on the occurrence and development of tumors. In our study, we found HBB expressions were down-regulated in both lung cancer tissues and plasma samples, this was consistent with the report by Kang et al 9 The expression HBB had a high diagnostic value in lung cancer by ROC curve analysis. Moreover, the combination of HBB and CEA was more significant than HBB or CEA alone in the diagnosis of lung cancer.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 23 These results indicated that HBB had an inhibitory effect on the occurrence and development of tumors. In our study, we found HBB expressions were down-regulated in both lung cancer tissues and plasma samples, this was consistent with the report by Kang et al 9 The expression HBB had a high diagnostic value in lung cancer by ROC curve analysis. Moreover, the combination of HBB and CEA was more significant than HBB or CEA alone in the diagnosis of lung cancer.…”
Section: Discussionsupporting
confidence: 93%
“…It had been found that HBB could suppress the proliferation of nonsmall-cell lung carcinoma through P38/MAPK and JNK pathways. 9 The objective of our research is to verify the potential of HBB as a molecular indicator for diagnosing and prognosticating lung cancer, as well as its role in modulating cellular proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…It includes 43 COPD and 39 normal control samples, we found 956 DEGs (including 478 up regulated genes and 478 down regulated genes). HBB (hemoglobin subunit beta) [52], HLA-DQA1 [53], EGR1 [54], ATF3 [55], XIST (X inactive specific transcript) [56], CD163 [57] and S100A8 [58] plays a crucial role in the pathogenesis of lung cancer and considered a promising target for pharmacological based therapies. HBB (hemoglobin subunit beta) [59], HBA1 [60], HLA-DQA1 [61], EGR1 [62], ATF3 [63], XIST (X inactive specific transcript) [64], S100A12 [65], CD163 [66] and S100A8 [67] are closely related to the progression of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all DMR genes we found to be related to the gas transport were the genes encoding subunits of hemoglobin, which transports oxygen. One of these genes, HBB, is reported to be abnormally expressed in many cancer types [46][47][48] . This result suggests the possibility that genes frequently altered in cancer, although not directly related to the developmental process, can also be regulated by open sea CpG probes.…”
Section: Functional Annotation Of Dmr Genesmentioning
confidence: 99%